A survey of physician experience and treatment satisfaction using fast-acting insulin aspart in people with type 1 or type 2 diabetes. Issue 4 (18th May 2020) - Baru, Ankita; Amir, Sadaf; Ekelund, Magnus; Montagnoli, Roberta; Da Rocha Fernandes, João Diogo
ABSTRACT: Aims: This survey aimed to explore real-world physician experiences and treatment satisfaction with fast-acting insulin aspart (faster aspart) in clinical practice across Europe and Canada. Materials and methods: An online web-based survey was used for physicians treating people with type 1 or type 2 diabetes. General practitioners and specialists, with experience using faster aspart, were interviewed. Results: A total of 191 physicians participated in the survey. Most of their patients (68% of those with T1D and 63% of those with T2D) were previously treated with another mealtime insulin before switching to faster aspart. At the time of initiating faster aspart, nearly half of patients had an HbA1c level between 7.5% (59 mmol/mol) and 8.5% (69 mmol/mol). The main prescription drivers for faster aspart, versus other mealtime insulins, were faster onset of action, improved postprandial glucose (PPG) control, and dosing flexibility. Most physicians were more satisfied with faster aspart than other mealtime insulins regarding at-meal (66%) and post-meal (71%) dosing flexibility, improved PPG levels (66%), and onset of action (61%). Main reasons for not prescribing faster aspart included a good response to current treatment (76%) or patient reluctance to switch (57%). Overall, 12% of patients discontinued faster aspart, for reasons including concerns of hypoglycemia (17%), poor adherence (17%), and level of patient co-pay (17%). More than half of physicians had fewer concerns regarding postprandial hyperglycemia, and were more confident in their patients reaching their HbA1c target with faster aspart than with other mealtime insulins. Limitations: The findings of this survey are based heavily on physicians' experiences, and could therefore be subject to recall bias. Conclusions: Reported physician and patient experiences of using faster aspart have been positive, and better PPG control and increased dosing flexibility are expected to improve glycemic management.